2005
DOI: 10.1063/1.2051802
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation study of nanofibers

Abstract: Nanoindentation study of a single poly(L-lactic acid) nanofiber produced by the phase separation method was performed using an atomic force microscope (AFM) cantilever tip. Issues concerning the use of AFM for nanoindentation of polymer nanofibers were discussed. The Hertz theory of contact mechanics was used to analyze the indentation results. It was found that the elastic modulus was comparable to that obtained from the nanoscale three-point bend test done in our previous study, after roughness correction wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 18 publications
1
58
0
Order By: Relevance
“…87 In these tests, an AFM probe is commonly used to indent the nanofiber, but many factors must be controlled, such as the humidity, the underlying surface, and the fiber surface roughness. 13 Due to the technical difficulties of mechanical testing of individual nanofibers, models that could accurately predict the mechanical properties of fibers based on the fiber diameter, structure, material composition, and processing techniques would have much utility in the field of tissue engineering. Such models are underdeveloped but would allow more knowledge to be gained from how the mechanical properties of individual fibers influence fiber-cell interactions.…”
Section: Mechanical Characterizationmentioning
confidence: 99%
“…87 In these tests, an AFM probe is commonly used to indent the nanofiber, but many factors must be controlled, such as the humidity, the underlying surface, and the fiber surface roughness. 13 Due to the technical difficulties of mechanical testing of individual nanofibers, models that could accurately predict the mechanical properties of fibers based on the fiber diameter, structure, material composition, and processing techniques would have much utility in the field of tissue engineering. Such models are underdeveloped but would allow more knowledge to be gained from how the mechanical properties of individual fibers influence fiber-cell interactions.…”
Section: Mechanical Characterizationmentioning
confidence: 99%
“…15 Previous studies concerning the determination of Young's modulus of single electrospun polymeric fibers have found that the Young's modulus of fibers is regulated by the diameter of the fibers. 12,14,28,29 The mechanical behaviour of electrospun fibers was found to be a consequence of the changes in orientation of the polymer molecules during the electrospinning process provided by the strong strain forces of the polymer jets. 29 The high strain rate of the ejected polymer jets induces a molecular orientation of polymer nanofibers along the fiber axis.…”
Section: 25mentioning
confidence: 99%
“…7) and to be 133 kPa when determined following the Hertz theory on an equivalent homogeneous sphere. 7 For comparison, the elastic modulus determined for electrospun nanofibers made of synthetic polymers, such as PLLA, PVA, and PAN, have been found to range from 0.5 to 0.9 GPa, 12 4 to 13 GPa, 13 and 5.72 to 26.55 GPa, 14 respectively, depending on the size of the diameter of the fiber. In addition, electrospun nanofibers made of natural materials, such as proteins like gelatin, collagen, and elastin, exhibited a lower elastic modulus (tensile moduli), compared to synthetic polymers of approximately 426, 262, and 184 MPa, respectively.…”
Section: 25mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering a diameter of nanofibres, atomic-force-microscopy (AFM) based tests, such as nano-tension [18], nano-bending [19,20], nanoindentation [21], together with custom-made nano-testing systems [22,23] were employed instead of commercial mechanical-testing systems. For BC nanofibres, in an early study, Guhados et al [24] measured their axial modulus by performing nanoscale-three-point-bending tests using an AFM cantilever; the obtained magnitude was 78 ± 17 GPa.…”
Section: Introductionmentioning
confidence: 99%